Test and analysis of energy characteristics of large vertical submersible pumps - Yang, Chen; Lingyu, Li; Huixiang, Chen; Dan, Su (Frontiers in Energy Research, 2024)
The efficiency of the pump device is an important parameter to judge the overall dynamic performance of the pumping station. The commonly used method at home and abroad is to carry out model tests of the pump device. The performance parameters of the prototype pump and pump device are obtained by the similarity conversion formula. However, at present, there are not many device model tests for large vertical submersible pumps. Taking a large vertical submersible mixed-flow pumping station in China as an example, research predicted the performance of the pump device through a model test and a submersible pump prototype test. The results show that the model test of the large vertical submersible mixed-flow pump device has a maximum efficiency of approximately 77.8%, and the prototype test conversion device has a maximum efficiency of approximately 80.33%. The device model test and the pump factory prototype test results are compared. It is found that the performance parameters of the pump measured by the prototype test are in good agreement with the device model test under the design conditions, and there is a certain error when the deviation from the design conditions is significant. The device model test and the factory test of the pump are indispensable in the large-scale road of submersible pumps, and a large number of tests are needed to sum up the experience.